Complicated upper extremity deep vein thrombosis (Paget-Schroetter disease): a case report - L. I. Syromyatnikova; E. Kh. Aliev; O. M. Lapin; S. A. Mekhryakov (Российский кардиологический журнал)
We report the case of the development of pulmonary embolism in a patient with Paget-Schroetter disease.